2017
DOI: 10.1016/j.clinthera.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Declining Skeletal Muscle Function in Diabetic Peripheral Neuropathy

Abstract: Purpose In this review, we highlight the current concepts in the effects of diabetic peripheral neuropathy (DPN) in skeletal muscle. We discuss the lack of effective pharmacological treatments and the role of physical exercise intervention in limb protection and symptom reversal. We also highlight the importance of Magnetic Resonance Imaging (MRI) techniques in providing a mechanistic understanding of the disease and helping develop targeted treatments. Methods This review provides a comprehensive reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 175 publications
(255 reference statements)
6
32
0
1
Order By: Relevance
“…Although these structural nerve abnormalities are apparent, few studies have explored the effect on skeletal muscles. In a few related studies, our findings are supported by one that found muscle disruptions in Charcot–Marie‐Tooth neuropathy (Pareyson et al ) and some that have shown declines in skeletal muscle quantity and quality in patients with diabetic peripheral neuropathy (Moore et al ; Parasoglou et al ). Thus, reductions in muscle quantity and quality are likely driven by CIDP‐related neural factors, such as motor axon loss (Gilmore et al ) and impaired neural signaling perhaps related to nerve lesions or segmental demyelination as reported in prior studies that presumably lead to accelerated muscle atrophy (Pitarokoili et al ).…”
Section: Discussionsupporting
confidence: 84%
“…Although these structural nerve abnormalities are apparent, few studies have explored the effect on skeletal muscles. In a few related studies, our findings are supported by one that found muscle disruptions in Charcot–Marie‐Tooth neuropathy (Pareyson et al ) and some that have shown declines in skeletal muscle quantity and quality in patients with diabetic peripheral neuropathy (Moore et al ; Parasoglou et al ). Thus, reductions in muscle quantity and quality are likely driven by CIDP‐related neural factors, such as motor axon loss (Gilmore et al ) and impaired neural signaling perhaps related to nerve lesions or segmental demyelination as reported in prior studies that presumably lead to accelerated muscle atrophy (Pitarokoili et al ).…”
Section: Discussionsupporting
confidence: 84%
“…However, executive dysfunction is probably not the only factor responsible for the reduced TUG scores observed in the current study since T2DM progression synergistically with prolonged hyperglycemia exposure is known to result in diabetic peripheral neuropathy, which is associated with several deficiencies in the morphology and functioning of the skeletal muscle—such as denervation-reinnervation process and loss of motor axons and nerve excitability and conduction (i.e., demyelination)—resulting in accelerated muscle atrophy and fatigue and loss of muscle strength and power (i.e., muscle weakness), consequently reducing motor function (e.g., walking, climbing stairs) [ 2 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The progression of T2DM leads to the development of poor outcomes, such as diabetic peripheral neuropathy, which is known by its deleterious effects on muscle architecture and functioning, reducing muscular functionality (e.g., mobility, transfer capacity) [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Revista Saúde e Pesquisa, v. 11, n. 3, p. 451-457, setembro/dezembro 2018 -ISSN 1983-1870 -e-ISSN 2176-9206 com maior frequência no GNT (85,7%) quando comparado ao GT (21,4%), e maior frequência de DM. Evidência demonstra que o DM promove a redução do VO 2 , além de resultar em diminuição da capacidade cardiorrespiratória e da tolerância ao exercício 18,20 . Isso ocorre pela insuficiência e/ou utilização incorreta da insulina, o que pode acarretar em uma série de distúrbios relacionados à síntese da glicose ingerida dos alimentos, prejudicando sua utilização como energia pelo nosso organismo 19,21 .…”
Section: Artigos Originaisunclassified